Maternal Life-Histories of Multiple Birth Mothers Compared to Singleton Only Mothers in 19th and Early 20th Century Netherlands - Peter Ekamper; Frans van Poppel (Historical Life Course Studies)
Research on mothers of twins suggests they have a more robust phenotype compared to singleton only mothers. Historical demographic microdata can be of additional value in studying differences in reproductive behaviour and survival of their offspring between multiple birth mothers and singleton only mothers. However, the number of such studies in historical populations is limited. This study aims to explore the possibilities to study maternal life-histories of multiple birth mothers compared to singleton only mothers using microdata on 19th and early 20th century Netherlands from the HSN/LINKS database. In line with studies on other historical populations, our results confirm multiple birth mothers on average had their first birth at younger ages, their last birth at older ages, longer reproductive lifespans, shorter inter-birth intervals, and higher lifetime fertility than singleton only mothers.